Optimising the use of irrigated lands in Kazakhstan: system analysis and resource management (Journal of Economic Research & Business Administration, 2024)
This article explores the challenges and opportunities in optimizing the use of irrigated lands in Kazakhstan, focusing on system analysis and resource management. The research purpose is to identify strategic improvements in irrigation practices and regional water governance, while aiming to enhance water resource management efficiency and sustainability in agriculture. The main directions of the study involve analyzing Kazakhstan's reliance on external water sources, infrastructural inefficiencies, and region-specific strategies for sustainable agricultural practices. Methodologically, the research relies on regional case studies, national statistical data, and quantitative analyses, including correlations and descriptive statistics. It also applies frameworks like Integrated Water Resources Management, Socio-Ecological Systems, Water-Energy-Food Nexus, and Participatory Water Management.The research results highlight Kazakhstan's vulnerability due to its significant dependence on external water sources, accounting for 46% of its water supply, and inefficiencies in its aging irrigation infrastructure. The practical value of this research is in offering comprehensive, actionable recommendations to policymakers, agricultural stakeholders, and local communities for improving infrastructure, adopting efficient irrigation techniques, and fostering international collaboration. The research novelty lies in its interdisciplinary application of multiple strategic frameworks to develop tailored strategies addressing the unique challenges across Kazakhstan's economic districts, balancing agricultural productivity with sustainable water management practices.Key words: water resource management in Kazakhstan, agricultural water efficiency and sustainability, impact of external water sources, innovation in irrigation practices, economic problems in agriculture.